Transcriptomics and metabolomics analysis reveal the anti-oxidation and immune boosting effects of mulberry leaves in growing mutton sheep - Cui, Xiaopeng; Yang, Yuxin; Zhang, Minjuan; Liu, Shuang; Wang, Hexin; Jiao, Feng; Bao, Lijun; Lin, Ziwei; Wei, Xinlan; Qian, Wei; Shi, Xiang; Su, Chao; et al. (Frontiers in Immunology, 2023)
Currently, the anti-oxidation of active ingredients in mulberry leaves (MLs) and their forage utilization is receiving increasing attention. Here, we propose that MLs supplementation improves oxidative resistance and immunity. We conducted a trial including three groups of growing mutton sheep, each receiving fermented mulberry leaves (FMLs) feeding, dried mulberry leaves (DMLs) feeding or normal control feeding without MLs. Transcriptomic and metabolomic analyses revealed that promoting anti-oxidation and enhancing disease resistance of MLs is attributed to improved tryptophan metabolic pathways and reduced peroxidation of polyunsaturated fatty acids (PUFAs). Furthermore, immunity was markedly increased after FMLs treatment by regulating glycolysis and mannose-6-phosphate pathways. Additionally, there was better average daily gain in the MLs treatment groups. These findings provide new insights for understanding the beneficial effects of MLs in animal husbandry and provide a theoretical support for extensive application of MLs in improving nutrition and health care values.